Exposer le maïs quotidien ? - Serge Bahuchet; Ingrid Arriaga; Pauline Rameau; Estefanía Angeles (Revue d'ethnoécologie)
In 2019, the Cultural Institute of Mexico (CIM) in Paris and researchers from the MNHN's Eco-anthropology laboratory produced an ambitious exhibition, Maiz de mis amores, dedicated to evoking the place of this major food plant in the daily life of contemporary Mexico. This exhibition was based on the collection of objects gathered during field trips and the photographs taken at that time. This article situates this project in the current research conducted by the laboratory in Mexico, explains the approach from the point of view of the CIM and explains the museological and scenographic choices that led to the exhibition. The exhibition is then detailed in the form of an illustrated tour.